(3PcQ CSeGA GdJGHYjf hef HYOge ef UMJ QhGjJg ef GdKbGJ YfO GdHNGQj heSde hPcQGg aj cJGHjgeG GdUMjMjf Ch CMOgeG QhGjI CHj WGdH eMeO Hf Ydj Hf GdaJM GdMQHj GdeYQha GdeYQha HGdYKGQjs - (3GdOGQbWfj, CHh GdMSf, Ydj Hf YeQ Hf CMeO, J (B385(3g`s
(3BNQgG (B:s
(3YdjgG aj GdBNQ(B: (3CfgG fbdJ Yf fSNI fbdJ HNW(B: (3GdMejOj, hYhQV HgG, hfSNI GdNI GdMejO efbhdI ef CUd jNW GdOGQbWfj heYGQVI Hgs
(3eUOQ GbJfGA GdCUd (B:s
(3aGVd CMeOs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdMOjK hGdeUWdMs